Proceedings of the 58th Annual Meeting of the Association for Computational Linguistics 2020
DOI: 10.18653/v1/2020.acl-main.462
|View full text |Cite
|
Sign up to set email alerts
|

(Re)construing Meaning in NLP

Abstract: Human speakers have an extensive toolkit of ways to express themselves. In this paper, we engage with an idea largely absent from discussions of meaning in natural language understanding-namely, that the way something is expressed reflects different ways of conceptualizing or construing the information being conveyed. We first define this phenomenon more precisely, drawing on considerable prior work in theoretical cognitive semantics and psycholinguistics. We then survey some dimensions of construed meaning an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…comment negative sentiment) and use them as separate features for prediction. LIWC The linguistic styles and word choices that speakers choose to convey their intent can reflect how they conceptualize meaning (Trott et al 2020). Prior studies suggested that information gained from examining these lexical patterns can be useful in contentiousness prediction (Addawood et al 2017;Addawood and Bashir 2016).…”
Section: Linguistic Operationalizationmentioning
confidence: 99%
“…comment negative sentiment) and use them as separate features for prediction. LIWC The linguistic styles and word choices that speakers choose to convey their intent can reflect how they conceptualize meaning (Trott et al 2020). Prior studies suggested that information gained from examining these lexical patterns can be useful in contentiousness prediction (Addawood et al 2017;Addawood and Bashir 2016).…”
Section: Linguistic Operationalizationmentioning
confidence: 99%
“…However, the notion of competence itself has received relatively little attention in recent NLP and AI frameworks, where focus has been on acquiring specific linguistic skills from a linear signal consisting essentially of surface forms. As pointed out by various researchers, the practice of applying statistical techniques to enormous amounts of text is unlikely to yield human-like language, including its relation to the world around us, its pragmatic nuances, or the fact that it can be acquired from very limited data [5,43,54]. The present paper seeks to provide a more encompassing computational framework by coming back to the main theories of competence in the linguistic literature, focusing specifically on the acquisition of meaning.…”
Section: Introductionmentioning
confidence: 99%